LandMOD ET mapper: A new matlab-based graphical user interface (GUI) for automated implementation of SEBAL and METRIC models in thermal imagery. (August 2019) - Bhattarai, Nishan; Liu, Tao
Abstract: Remote sensing based surface energy balance (SEB) models, such as SEB Algorithm for Land (SEBAL) and Mapping evapotranspiration (ET) at high Resolution with Internalized Calibration (METRIC) are widely used to monitor ET. However, their operational use is challenged by model complexity and the tedious process of selecting hot and cold pixels. We developed a new Matlab-based ET mapping toolbox named "LandMOD ET Mapper" for automated implementation of these models to facilitate their widespread applications among new users. The toolbox is demonstrated using one Landsat and one Moderate Resolution Imaging Spectroradiometer (MODIS) Terra image covering three AmeriFlux sites in Nebraska, U.S. Daily ET estimates were comparable with the observed ET for five days when near cloud-free Landsat and MODIS Terra images were available in the 2006 maize growing season. The toolbox provides a viable ET mapping option to new and inexperienced users with reduced time and labor demands. Highlights: A new Matlab-based GUI "LandMOD ET Mapper" was developed. The toolbox implements SEBAL/METRIC model automatically using thermal imagery. Daily ET estimates from the toolbox were comparable with observed ET.